Do eu ao não-eu: um estudo sobre os relatos dos efeitos da experiência do estado de rigpa (clara luz) segundo a tradição budista tibetana - Cruz, Júlia Signer e (2008)
This paper has as purpose to observe the psychological effects of the rigpa´s (clear light) experience among some Tibetan Buddhist practioners. As I didn t find academic researches with this object, this paper came to fullfill this fault. We use as theoretical base the Jung s psychology and the philosophy of Ati and Anutara Yogas of Tibetan Buddhism. Twenty two practioners, ages between 23 and 71 years old of both sexes were interviewed. The results allows us to conclude that rigpa s experience make possible to realize the human existence in a more open way where the Consciousness is fixed in a place deeper than the ego, what may produce a existential experience of union with the universe, a natural feeling of joy, freedom and well being, a body relaxation and a sense of mental openness with a spontaneously sense of natural wisdom